Gangs in the Latino Atlántico: Identity, Transnationalism and Generations - Queirolo Palmas, Luca (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2009)
This article is founded in the notion that the proliferation and growth of ‘street organizations’ around the world are connected to the construction of identities, the emergence of transnational lives and new forms of understanding generations. The first part of the article seeks to explain the  global  reproduction  of  these  groups,  which  start  as  local  organizations.  The second part answers to the specific question: What does it mean to be “latino”?,  in order to do that the experience of Latin Kings members is used. Finally, the author analyzes the way in which transnationalism is expressed in the day to day lives of those who belong to these groups.